2022
DOI: 10.1002/jpen.2385
|View full text |Cite
|
Sign up to set email alerts
|

Markers of respiratory function response to high‐carbohydrate and high‐fat intake in patients with lung diseases: a systematic review with meta‐analysis of randomized clinical trials

Abstract: Background Macronutrients can differently affect respiratory function markers such as VO2, VCO2, PaO2, PaCO2, and respiratory quotients (RQs), but systematic appraisal of the evidence on randomized clinical trials (RCTs) is lacking. Objective The objective of this work is to compare the response of respiratory function markers with high‐carbohydrate and high‐fat intake in patients with lung diseases. Methods Systematic review conducted according to Cochrane Collaboration recommendations, reported following Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Regarding dietary fiber, it was decided that providing a lower indication than that provided by the Livelli di Assunzione di Riferimento di Nutrienti ed energia (LARN; National Recommended Energy and Nutrient Intake Levels) was preferred to encourage the intake of energy and protein foods, especially considering the difficulties met by patients with COPD in feeding and the early sense of satiety as a result of high-fiber food intake. Compared to the LARN, a higher intake of lipids was recommended, especially for phenotypes presenting with a partial pressure of carbon dioxide of >50 mm Hg, a measure of carbon dioxide in arterial or venous blood [ 53 ]. For saturated fats, a maximum intake of 10% of total daily calories was suggested according to LARN guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding dietary fiber, it was decided that providing a lower indication than that provided by the Livelli di Assunzione di Riferimento di Nutrienti ed energia (LARN; National Recommended Energy and Nutrient Intake Levels) was preferred to encourage the intake of energy and protein foods, especially considering the difficulties met by patients with COPD in feeding and the early sense of satiety as a result of high-fiber food intake. Compared to the LARN, a higher intake of lipids was recommended, especially for phenotypes presenting with a partial pressure of carbon dioxide of >50 mm Hg, a measure of carbon dioxide in arterial or venous blood [ 53 ]. For saturated fats, a maximum intake of 10% of total daily calories was suggested according to LARN guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…High fat intake has been associated with significantly improved of respirator function markers (reduction of VCO 2 , VO 2 , PaCO 2 , and respiratory quotients [RQs]) in patients with lung cancer. 14 Although all patients received personalized nutritional advice, only the mirtazapine group achieved a significant improvement in fat source of energy at 8 weeks compared with placebo.…”
Section: Discussionmentioning
confidence: 98%
“…In this double-blind randomized clinical trial, there was no difference in appetite scores in patients who received mirtazapine or placebo, but only the mirtazapine group registered a significant increase in energy intake through the 4 weeks of follow-up, and was maintained after 8 weeks, mainly in fat intake, which is a better and crucial source of energy. High fat intake has been associated with significantly improved of respirator function markers (reduction of VCO 2 , VO 2 , PaCO 2 , and respiratory quotients [RQs]) in patients with lung cancer . Although all patients received personalized nutritional advice, only the mirtazapine group achieved a significant improvement in fat source of energy at 8 weeks compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…1 Mechanisms by which KD improves OHS theoretically include (1) lower V ̇CO 2 , (2) the stimulatory effects of ketone bodies on 12 In this study, KD lowered RQ from 0.81 to 0.75, and P v CO 2 was linearly related to RQ. Prior studies have demonstrated that altering macronutrient composition affects CO 2 homeostasis in respiratory disorders 13 with high carbohydrates intake compromising functional outcomes. [14][15][16][17] A caloric deficit in its own right also reduces V ̇CO 2.…”
Section: Discussionmentioning
confidence: 99%